Penerapan Terapi Musik Pada Warga Binaan Pemasyarakatan Rutan Kelas 1 Makassar - Cindy Caroline; Misly Megautari Putri; Surya Algazali Akbar; Perdana Kusuma (Literasi Nusantara Publisher, 2022)
Every Indonesian citizen is obliged to obey all rules according to applicable law. Drugs are addictive substances that can ensnare anyone regardless of age. A person who abuses drugs will be processed according to the existing law and placed in the Detention Centre (Rutan) during the process of investigation, prosecution, and examination in court. Drug abuse makes users feel hallucinations, stimulants, depressants, and addiction. Several inmates at the Class 1 Rutan Makassar explained that there were several negative emotions they felt including feelings of depression, anxiety or anxiety, loss of self-confidence, and reluctance to socialize. Music therapy is an intervention that can be done for clients to improve their physical and emotional health. Several studies have shown that music can be used as therapy because it is effective in overcoming psychological problems. The purpose of this therapy is to find out the impact that is felt after receiving the application of music to the inmates at the Class 1 Rutan Makassar. Participants were as many as 19 correctional inmates with drug abuse cases of the male gender. The result of this activity was that the participants were enthusiastic and focused on the facilitator's instructions. The participants' expressions can be seen when shedding tears and smiling while listening to music. Participants felt positive impacts including feeling calm, safe, peaceful, satisfied, comfortable, confident, relaxed, feeling enough, strong, and happy to participate in activities. Participants also felt happy and satisfied with the activities carried out and thanked the facilitator team.